2022
DOI: 10.3390/nu14061268
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Nutritional Risk Index, Geriatric Nutritional Risk Index, BMI, and GLIM-Defined Malnutrition in Predicting Survival of Patients with Head and Neck Cancer Patients Qualified for Home Enteral Nutrition

Abstract: Malnutrition is a poor prognostic factor in cancer disease. In case of head and neck cancer, there are multiple disease symptoms and side effects of treatment that increase the risk of malnutrition. The aim of the study is to assess the association between nutritional status at the time of qualification for home enteral nutrition (HEN) and overall survival of patients with head and neck cancer (HNC), and assessment usefulness of selected nutritional indices as prognostic factors. The retrospective survival ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…Patients in the high NRI group had a significantly better OS than those in the low NRI group. Consistent with the results of previous studies in other cancers, our results suggest that malnutrition, as assessed by the NRI, may be a predictor of poor survival in patients with NDMM [ 22 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Patients in the high NRI group had a significantly better OS than those in the low NRI group. Consistent with the results of previous studies in other cancers, our results suggest that malnutrition, as assessed by the NRI, may be a predictor of poor survival in patients with NDMM [ 22 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study suggested that GNRI could be utilized in clinical setting in the future for confirming ESCC patients with decreasing nutrition level and for patients who requiring nutritional support before esophagectomy. Przekop et al ( 24 ) had proved that GNRI could provide useful prognostic information in patients with head and neck cancer patients qualified for home enteral nutrition (HEN), and they had also suggested nutritional management should be also initiated earlier during the management of cancer patients. Liu et al ( 25 ) demonstrated that HEN and preoperative nutritional support was safe, and beneficial to the recovery of EC patients who had underwent esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…HNSCC can lead to dysphagia, dysgeusia, xerostomia, and oral mucositis, which can be caused directly by the primary tumor or due to treatment side effects, particularly from radio- and chemotherapy. These symptoms can severely impair daily calorie intake and are associated with increased mortality and morbidity [ 2 , 3 ]. Since a significant proportion of HNSCC patients require food supplements and tube feeding during treatment, managing their nutrition is an integral part of therapy.…”
Section: Introductionmentioning
confidence: 99%